Scientific communication and scientific literacy for the public perception of the importance of environmental quality for public health - Lopes, Renato Matos; Comarú, Michele Waltz; Pierini, Max Fonseca; de Souza, Raphael Argento; Hauser-Davis, Rachel Ann (Frontiers in Communication, 2024)
The interplay between environmental degradation, social disparities, and disease emergence, has become clearer than ever in the last decades, emphasizing the need for scientific approaches to protect human and environmental health. Despite scientific consensus, however, the general public often lacks awareness and understanding of these relationships. Misinformation and compartmentalized knowledge further complicate conveying the importance of the subject to the lay population. Thus, scientists must engage in effective scientific communication and promote scientific literacy (SL) among the public. This study discusses the strategies that may be employed to overcome disinformation and enhance scientific literacy and communication, all of which are paramount to deepen the understanding of the connections between biodiversity conservation, environmental health, and public well-being, empowering individuals to take informed actions for a sustainable and healthy future.